Gender and occupational allergy: Report from the task force of the EAACI Environmental and Occupational Allergy Interest Group. Issue 11 (6th November 2020) - Moscato, Gianna; Apfelbacher, Christian; Brockow, Knut; Eberle, Chiara; Genuneit, Jon; Mortz, Charlotte G.; Quecchia, Cristina; Quirce, Santiago; Siracusa, Andrea; Tarlo, Susan Mary; van Kampen, Vera; Walusiak‐Skorupa, Jolanta; et al.
Abstract: Women's work has traditionally been considered less hazardous to health in comparison with men's work. The increased women's participation in the workforce has led to an increased attention to women's working conditions. Women and men are unequally represented in individual professions or sectors (horizontal segregation), with women also under‐represented in leadership positions (vertical segregation). The selection of specific occupations can result in differences between types and levels of occupational exposures among women and men and can affect prevalence of occupational allergy. Gender distribution of work‐related asthma appears to vary across countries without clear global difference. Occupational rhinitis tends to be higher in women, although is not clear if this is related to a sex/gender effect or to differences in work exposure. Women are more likely to have occupational contact dermatitis, mainly due to wet work. No clear effects of gender on rates of hypersensitivity pneumonitis have been shown. Besides variation in exposures, physical and physiological characteristics, different behaviours and health consciousness have an impact on the occupational health hazards of women and men. Occupational allergy health promotion strategies need to consider approaches for women and men adjusted by gender, and legislative actions similarly could be implemented in a more gender‐sensitive way.